PERAN INOVASI SEBAGAI MEDIASI HUBUNGAN ANTARA MODAL INTELEKTUAL DENGAN KEUNGGULAN BERSAING UKM - Sugiono, Edi; Efendi, Suryono; Sumardi, Rebin (Economic Faculty, Attahiriyah Islamic University, 2019)
The purpose of this paper is to examine the impact of all variable intellectual capital (human capital, structural capital, and relational capital) on the competitive advantage through the mediating innovationsmall and medium enterprises (SMEs) in the Jombang area. Primary data was obtained from the 100 SME’s leader in Jombang. Hypothesis testing is done by using Partial Least Square Structural Equation Modeling (SEM-PLS). The results of the study show that all variable intellectual capital (human capital, struktural capital, dan relational capital) have a positive and significant effect on improving SMEs’ competitive advantage.significant effect on improving SMEs’ competitive advantage. The results of this study also prove that innovation can mediate the relationship between all variable intellectual capital (human capital, structural capital, and relational capital) and SMEs’ competitive advantage. Keywords: Intellectual capital, innovation, competitive advantage